Support of Research Activities of Future Teachers through Organization of Tutoring - A. A. Kadyseva; E. V. Ermakova; O. S. Kozlovtseva; L. V. Gubanova (Научный диалог)
The attitude of future teachers to research activities during their studies at the university is analyzed on the example of Ishim Pedagogical Institute named after P. P. Ershov. Features of support of students at the choice of research trajectories are considered. Students’ attitude to scientific research is characterized. Necessary conditions for effective work of students on scientific projects are revealed. The necessity of introduction of scientific tutorship since the first year of training, and also attraction of students of senior courses who achieved certain scientific results as tutors is shown. The article deals with the tutor’s activity as a consultant, mentor and organizer of the student’s independent activity in the organization of scientific research. The article describes the experience of the organization of tutoring on the example of a pedagogical university, where not only teachers work as mentors, but also so-called “academic consultants” do - senior students who have their own positive experience in conducting research. The studies were conducted with the participation of 200 respondents from the number of full-time students from 1 to 5 course. In the course of research the main directions of activization of research activity of students are found out.